Prediction of the elastic-plastic behavior of thermoplastic composite laminated plates ([0°/?°]2)with square hole - Arslan, N; Çelik, M; Arslan, N (Elsevier Sci Ltd, 2002)
An elastic-plastic stress analysis in symmetric and antisymmetric woven-reinforced polyethylene thermoplastic matrix composite is studied by using finite element method (FEM) and first-order shear deformation theory for small deformations. The thermoplastic matrix composite layer reinforced by long stainless steel fiber is manufactured by using molds under the action of 15 MPa pressure and heating up to 160degreesC. The laminated plate ([0degrees/thetadegrees](2)) with square hole consists of four composite layers and bonded symmetrically and antisymmetrically. Each layer with constant thickness is meshed into 64 elements and 288 nodes with simply supported and in-plane loading conditions. The loading and reinforcement angle are gradually increased from the yield point of the plate. The load steps increased as 0.01 MPa at each iteration are selected as 100, 200, 300 and 400. The expansions of plastic zones and residual stresses are obtained according to load steps and orientation angles. The intensity of the residual stress components is maximum near the square hole. (C) 2001 Published by Elsevier Science Ltd.
Keywords: residual stress; plastic zone; thermoplastic laminated composite; elasto-plastic stress analysis; finite element method; square hole